Uji Aktivitas Antidiabetes Ekstrak Etil Asetat Daun Lamun (Enhalus acoroides) Pada Mencit (Mus musculus) - Hamsidar Hasan; A.Mu'thi Andy Suryadi; Zulfianto Djufri (Journal Syifa Sciences and Clinical Research, 2022)
Diabetes mellitus is a severe condition, chronic in nature, that occurs when there is an increase in blood glucose levels (GDS) 200 mg/dL or hyperglycemic conditions. Some plants are reported to have anti-diabetic effects. One of the examples is seagrass (Enhalus acoroides), which has α-glucosidase enzyme inhibitory effects in vitro. The community often uses it as traditional medicine. This present work explores the anti-diabetic activity of ethyl acetate extract of seagrass (Enhalus acoroides) leaves against male mice (Mus musculus) charged with 90% sucrose solution. It employed the oral sucrose tolerance test (OSTT) methodology. Activity tests on mice were carried out in five treatment groups, namely: group I or a negative control (Na-CMC 1% w/v); group II or a positive control (acarbose); group III (ethyl acetate extract dose 50 mg/kg BW); group IV ( ethyl acetate extract at a dose of 150 mg/kg BW), and; group V (ethyl acetate extract at a dose of 250 mg/kg BW). All data were analyzed by using a one-way ANOVA statistical test. The results show that the ethyl acetate extract of seagrass leaves can inhibit the absorption of sucrose, in which the most significant total inhibition occurred at a dose of 250 mg/kg BW, i.e., 68 mg/dL. A substantial inhibition was also found at a dose of 150 mg/kg BW, which was 82 mg/dL and at a dose of 50 mg/dL or 103 mg/dL. In conclusion, the ethyl acetate extract of seagrass leaves has anti-diabetic activity.